2006
DOI: 10.1111/j.1467-2494.2006.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of taurine on human hair follicle grown in vitro1

Abstract: Taurine is a naturally occurring beta-amino acid produced by methionine and cysteine metabolism. It is involved in a variety of physiological functions, including immunomodulatory and antifibrotic. Taking advantage of the ability of human hair follicle grown in vitro to recapitulate most of the characteristic features of normal hair follicle in vivo, we studied (i) taurine uptake by isolated human hair follicles; (ii) its effects on hair growth and survival rate; and (iii) its protective potential against tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This lotion contains also taurine. This amino acid has several positive effects on hair bulb and hair growth [26]. These active components of the GFM-L are conveyed in nanosomes, which allow the rapid absorption and a deep release into the follicle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lotion contains also taurine. This amino acid has several positive effects on hair bulb and hair growth [26]. These active components of the GFM-L are conveyed in nanosomes, which allow the rapid absorption and a deep release into the follicle.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of this lotion in subjects treated with PRP can amplify the growth hair stimulus but also counteract some negative actions on hair physiology of some components of PRP for example the TGF-β. Collins et al [26] have demonstrated that taurine blocks the deleterious effect of TGF-β on human hair follicule. Some limitations should be taken in account in evaluating our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the epidermis, a gradient was evident with maximal levels of TAUT in the outermost granular keratinocyte layer and lower levels in the stratum spinosum, but no TAUT was found in the basal layer. Taurine has shown to play an important role not only in the keratinocyte hydration but also to act as a protective agent against transforming growth factor (TGF)-β1, an inhibitor of in vitro hair growth (8). The survival rate in vitro was increased when isolated hair follicles are grown in the presence of taurine.…”
Section: Introductionmentioning
confidence: 98%
“…Chemically selective detection of molecular agents in the hair has been achieved using techniques such as autoradiography7 and micro X-ray fluorescence analysis in combination with high-resolution SEM 8. Although such probing techniques are useful for determining the location of certain chemicals in the hair, they require sample preparation methods that can compromise the three-dimensional structure of the hair, obscuring a direct correlation between the distribution of the chemical and the morphology of the hair.…”
Section: Introductionmentioning
confidence: 99%